Can Keyboarding Skills Improve Student Performance and Engagement? - Sholikah, Mar'atus; Mubais, Ahmad; Kurniawan, Indra; Susanti, Anis (Journal of Office Administration : Education and Practice, 2023)
Lecturers must create innovative and engaging learning experiences that encourage students to actively participate in all aspects of the learning process so that student's academic performance can improve. This study tested the effectiveness of the blind system method assisted by 10astfingers learning media in improving students' performance and engagement. This study used a treatment-by-level design (T-LD). The subject of this study were 73 undergraduate students of business administration at Politeknik Balekambang Jepara. The data were collected through practicum tests and questionnaires. An independent sample test was used for data analysis This study showed that 10fastfingers learning media can improve students' cognitive and psychomotor performance. Thus, this medium is effective as a keyboard learning medium for improving student performance. The results of this study showed that 10fastfingers media were able to increase student participation in learning activities. Therefore, it can be concluded that use of 10fastfingers media can improve academic performance and student engagement.